Histological changes of the kidney in gentamycin induced nephrotoxicity and protected role of fish oil - Ahmed, Md Shameem; Eami, Eshrat Jahan (Central Medical College Journal, 2024)
Background: The kidneys are one of the vital organs of our body. The kidney contributes to the maintenance of homeostasis by a complex process that involves filtration, active absorption, passive absorption, secretion and the end result is the production of urine. Gentamicin induced acute renal failure is one of the kidney diseases which is very common not only in our country, also in worldwide. Gentamicin is the aminoglycoside of first choice because of its low cost and its reliable activity against all but the most resistant gram-negative aerobes. The fish oil is composed of eicosapentaenoic acid, docosahexaenoic acid & many more, may be one or more of these compounds has got nephro-protective action. This study may ensure the clinicians about safe use of gentamicin among those patients who are resistant to other antibiotics. Objective: To identify the histomorphological changes in the kidney in gentamicin-induced nephrotoxicity of the Long Evans rats and beneficial effect of fish oil against gentamicin-induced nephrotoxicity. Methodology: The study was carried out in the department of Anatomy, Dhaka Medical College (DMC), Dhaka, during the period from February 2005 to January 2006. The experiment was carried out on 40 healthy Long Evans rats. The rats were divided into six groups as Group: A, Group: B, Group: C and Group: D. Each group comprised of 10 (Ten) rats from either sex and was randomly selected. Results: In the present study showed that in normal saline control group of rats all the proximal tubules were normal but most of the proximal tubules showed necrotic changes that is about 77.67% of the tubules were necrotic in gentamicin treated nephrotoxic rats. It was also found that the fish oil treated groups showed less severe form of injury. Conclusion: Histologically kidney of experimental control group (gentamicin treated rats) showed proximal tubular necrosis. In the present study the fish oil showed the partial protection against the nephrotoxicity induced by gentamicin administered during the last 6 days of treatment with fish oil and by ameliorating the histopathological damage. Central Medical College Journal Vol 8 No 1 January 2024 Page: 12-16